PENGARUH KETINGGIAN TEMPAT DAN JENIS TERHADAP PENYUSUTAN ROTAN - M. Loiwatu (JURNAL HUTAN PULAU-PULAU KECIL, 2017)
Objective of the study was to determine shrinkage of three species of rattan, such as Tohiti (Calamus inops Becc), Batang Air (Daemonorops robustus Warb), Manau (Calamus manan Miq). Two factors was applied in the study was growing site (<100m, 100-200m, >200m) and species of rattan. Result of the study indicated that species of rattan was affected the shrinkage from green to air dry condition. Growing site was affected the shrinkage green to oven dry condition. Shrinkage from green to air dry condition was 1.25% -7.43% and shrinkage from air dry to oven dry condition was 0.37 % - 1.81 %.